International Myeloma Working Group Recommendations for the Diagnosis and Management of Solitary Plasmacytomas - Efstathios Kastritis; Shaji K. Kumar; Vincent S. Rajkumar; Wee Joo Chng; Luciano Costa; Monika Engelhardt; Wilson Gonsalves; Vania Hungria; Jens Hillengass; Dragan Jevremovic; Eirini Katodritou; Sigurður Yngvi Kristinsson; et al. (Journal of Clinical Oncology, 2026)
Solitary plasmacytomas (SPs) are rare localized tumors of clonal plasma cells, either in the bone (solitary bone plasmacytoma) or in soft tissue/extraosseous (extramedullary) with either no or with minimal bone marrow (BM) infiltration (